The effect of passive thoracic flexion-rotation movement on the total static compliance of the respiratory system and respiratory responses in ventilated patients - Bergh, Alison (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScPhysio (Physiotherapy))--University of Stellenbosch, 2007.